Evaluation of Final Income Tax on Construction Services Based on Government Regulation Number 9 of 2022 at CV. CIDA - MAWERU, Angela Lydia Stacia; BUDIARSO, Novi Swandari; SUWETJA, I Gede (Journal of Governance, Taxation and Auditing, 2023)
Government Regulation Number 9 of 2022 is the second amendment to Government Regulation Number 51 of 2008 concerning Income Tax on Income from Construction Services Business. This change is a policy issued by the Government to assist the Construction Services sector in dealing with the impact of the covid-19 pandemic so that this business process can be maintained. In this new regulation there are changes to the final income tax rate, classification and scope of construction services. This study aims to evaluate the application of the final income tax on construction services based on Government Regulation Number 9 of 2022 on CV. CIDA in this case the imposition of final income tax rate, calculation, withholding, deposit and reporting of final income tax on Construction Services. The research method used is descriptive qualitative method. The results of the study show that the final income tax rate imposed on CV. CIDA according to business qualifications and applicable regulations, namely 1.75%. For calculation, withholding and final income tax deposit CV. CIDA complies with existing regulations. However, the final income tax reporting is not in accordance with the existing tax regulations.